2020
DOI: 10.1093/nar/gkaa347
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic landscape and evolution of m6A methylation in human

Abstract: m6A is a prevalent internal modification in mRNAs and has been linked to the diverse effects on mRNA fate. To explore the landscape and evolution of human m6A, we generated 27 m6A methylomes across major adult tissues. These data reveal dynamic m6A methylation across tissue types, uncover both broadly or tissue-specifically methylated sites, and identify an unexpected enrichment of m6A methylation at non-canonical cleavage sites. A comparison of fetal and adult m6A methylomes reveals that m6A preferentially oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 62 publications
10
156
1
Order By: Relevance
“…To date, a few studies have evaluated the genome-wide m 6 A modification on skeletal muscle tissue in vivo, the dynamic change of m 6 A methylation in skeletal muscle development and the correlation between m 6 A and skeletal muscle are explored [14,103,110]. Many muscle-specific m 6 A sites have been identified in mammals [41,110,111]. In mouse, it's reported that the maternal high-fat diet alters the m 6 A pattern in skeletal muscle and adipose in a development-dependent way [112].…”
Section: The Dynamic Change and Potential Roles Of M 6 A Methylation In Skeletal Muscle Developmentmentioning
confidence: 99%
“…To date, a few studies have evaluated the genome-wide m 6 A modification on skeletal muscle tissue in vivo, the dynamic change of m 6 A methylation in skeletal muscle development and the correlation between m 6 A and skeletal muscle are explored [14,103,110]. Many muscle-specific m 6 A sites have been identified in mammals [41,110,111]. In mouse, it's reported that the maternal high-fat diet alters the m 6 A pattern in skeletal muscle and adipose in a development-dependent way [112].…”
Section: The Dynamic Change and Potential Roles Of M 6 A Methylation In Skeletal Muscle Developmentmentioning
confidence: 99%
“…As aforementioned, m 6 A modification is a dynamic and reversible epigenetic change ( Zhang et al, 2020 ), which affects the stability and function of RNAs, thereby modulating the pathogenesis and progression of diseases ( Qin et al, 2020 ; Wang et al, 2020 ; Zhu et al, 2020 ). M 6 A modification has been identified in more than 7,000 human genes, and it preferentially occurred at the site of stop codons and long internal exons within the RRACH sequence (R = G or A; H = A, C, or U) ( Dominissini et al, 2012 ).…”
Section: Rna M 6 a Modificationmentioning
confidence: 99%
“…Xia et al had generated 21 whole transcriptome m 6 A methylomes across major fetal tissues (Xiao et al, 2019 ); however, no adult tissues were included. Moreover, Zhang et al generated 27 m 6 A methylomes across major adult tissues (Zhang et al, 2020a ). Besides of protein coding genes, noncoding RNAs have been found to play important roles in development and cancer (Li et al, 2020 ; Xu et al, 2020a ; Zhang et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%